Lymphoepithelial Cyst of the Pancreas and Elevated Cyst Fluid Carcinoembryonic Antigen: A Diagnostic Challenge - Tewari, Nilanjana; Rollins, Katie; Wu, Jessie; Kaye, Phillip; Lobo, Dileep N (JOP. Journal of the Pancreas, 2014)
Context Pancreatic lymphoepithelial cysts are rare, benign cysts which can present diagnostic difficulties. Non-invasive imaging alone is unreliable in distinguishing between benign and malignant cysts. Endoscopic ultrasound (EUS) and fine needle aspiration (FNA) with analysis of cyst fluid is more reliable, but invasive. In addition, tumor markers such as carcinoembryonic antigen (CEA) can be grossly elevated in cyst fluid of benign cysts. Case report We present the case of a 67 year old man with an incidental finding of a pancreatic cyst. EUS and FNA-guided aspiration of cyst fluid was performed. Fluid CEA was grossly elevated and resectional surgery was performed. On histological examination the diagnosis was confirmed as lymphoepithelial cyst of the pancreas. Conclusion Tumor markers such as CEA can be elevated in the cyst fluid of benign pancreatic conditions such as lymphoepithelial cyst. Although the diagnosis is challenging preoperatively, if a systematic algorithm is followed, these conditions can be managed safely and efficiently. Image: Low power view of cyst lined by squamous epithelium with lymphoid tissue in wall and adjacent pancreatic lobule.